Wind tunnel experimental investigation of the aerodynamic coefficients reduction due to sheltering surroundings on a cruise ship moored in port. Issue 218 (November 2021) - Torre, S.; Burlando, M.; Ruscelli, D.; Repetto, M.P.; Camauli, G.
Abstract: The recent growth of cruise and container ships size, which is involving the shipping industry, determines the greater and greater importance of evaluating properly the wind actions on such big ships, especially during the mooring phase. Accidents and damages may occur in port areas during extreme wind events due to the breakage of mooring clamps, jeopardizing the safety of human beings and vessels as well as producing significant economic losses. Despite extreme winds are one of the main dangers for large ships within ports and standardised procedures to accurately assess wind loads are still missing. To shed light on this topic, a set of wind tunnel tests was carried out to investigate the shielding effect that the surroundings can play in reducing the wind forces acting on a 1:600 model of the large cruise ship in the Port of Monfalcone (Italy). The longitudinal and transversal forces and yaw moment were measured for three main sets of tests: (1) open sea condition; (2) ship and quay; (3) ship, quay, and other shielding ship upwind. The results showed a strong dependence of the wind load on the cruise ship according to different surrounding configurations. In particular, a reduction of the aerodynamic forces up to 60% for the wind directions orthogonal with respect to the ship was measured. On one hand, this demonstrated quantitatively that the shielding effects of complex surrounding buildings may guarantee an increase in port safety with the reduction of the overall forces acting on ships. On the other hand, it highlights the huge uncertainty which currently characterizes the assessment of wind loads in the mooring system design, pointing out that a novel approach should be adopted in which every mooring system is designed on a specific site-analysis base. Highlights: The aerodynamic behaviour of a new generation cruise ship is investigated. Wind tunnel tests are performed on the cruise ship with and without realistic surroundings. The methodology is validated with the most widely used approaches. Port surroundings shelter the ship reducing the lateral forces up to 60%.